Development of Interactive E-Modules Based on Heyzine Flipbook on the Potential of Indonesia's Natural Resources in Geography Learning for High School Students - Ady, Wulandari; Astutik, Sri; Nurdin, Elan Artono; Mujib, Muhammad Asyrofula; Susiati, Ana (Jurnal Pendidikan Geografi Undiksha, 2025)
This research is based on the lack of varied and innovative teaching materials and learning models that are still conventional. This research aims to produce an interactive teaching material product, namely the Heyzine Flipbook Based E-Module. This research is Research and Development (R&D) using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model developed by Reiser and Mollanda. Data collection instruments used expert validation questionnaires, student response questionnaires and learning outcomes questions. The results of the research carried out obtained values the validity assessment of media experts was 96.8% in the range of 90-100% and the validity level was "Very Valid". The validity assessment of material experts was 98.8%. The validity assessment of learning practitioners was 96.6%. The results of the small scale student response test were 94.3% and the large scale was 95.1%. The study results obtained that 33 students achieved learning completeness with a score of >75. These results show that student responses are positive and learning outcomes are very good.